Blackface, white noise Jewish immigrants in the Hollywood melting pot - Rogin, Michael Paul 1937- (A centennial book, 1996)
Immigrant Jews inherited the blackface role in vaudeville, Tin Pan Alley, and Hollywood; Blackface, White Noise treats burnt cork as their rite of passage to white America. Arguing against those who subsume racial under ethnic identities, Rogin demonstrates that blackface presided over an ethnically inclusive and racially exclusionary melting pot. Juxtaposing movies like The Jazz Singer with such early civil rights films as Pinky and Gentleman's Agreement, he shows how the blackface tradition infected even those motion pictures that wished to repudiate it